2017
DOI: 10.1080/09205063.2017.1354672
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor sequestration and enzyme-mediated release from genipin-crosslinked gelatin microspheres

Abstract: Controlled release of growth factors allows the efficient, localized, and temporally-optimized delivery of bioactive molecules to potentiate natural physiological processes. This concept has been applied to treatments for pathological states, including chronic degeneration, wound healing, and tissue regeneration. Peptide microspheres are particularly suited for this application because of their low cost, ease of manufacture, and interaction with natural remodeling processes active during healing. The present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 69 publications
4
43
1
Order By: Relevance
“…PL are rich in several chemokines and GFs such as platelet derived growth factor isoforms (PDGF-AA, -AB and -BB), transforming growth factor-β (TGF-β), insulin-like growth factor-1 (IGF-1), vascular endothelial growth factor (VEGF) and bone morphogenetic protein 2, -4 and -6 (BMP-2, -4, -6). Several works have suggested that PL are a valuable, non-xenogenic alternative to animal derived serum in cell culture(Bieback, 2013) (Turner, Thiele, & Stegemann, 2017) (Burnouf, Strunk, Koh, & Schallmoser, 2016) or combined with biomaterials (Santos, Sigurjonsson, Custodio, & Mano, 2018) (Oliveira, Santo, Gomes, Reis, & Mano, 2015). Physiologically, platelets are known to deliver a broad spectrum of GFs and have a main role in wound healing.…”
Section: Resultsmentioning
confidence: 99%
“…PL are rich in several chemokines and GFs such as platelet derived growth factor isoforms (PDGF-AA, -AB and -BB), transforming growth factor-β (TGF-β), insulin-like growth factor-1 (IGF-1), vascular endothelial growth factor (VEGF) and bone morphogenetic protein 2, -4 and -6 (BMP-2, -4, -6). Several works have suggested that PL are a valuable, non-xenogenic alternative to animal derived serum in cell culture(Bieback, 2013) (Turner, Thiele, & Stegemann, 2017) (Burnouf, Strunk, Koh, & Schallmoser, 2016) or combined with biomaterials (Santos, Sigurjonsson, Custodio, & Mano, 2018) (Oliveira, Santo, Gomes, Reis, & Mano, 2015). Physiologically, platelets are known to deliver a broad spectrum of GFs and have a main role in wound healing.…”
Section: Resultsmentioning
confidence: 99%
“…The release of molecules from the scaffold can be controlled by modifying the properties and composition of the material, TABLE 1 | List of common bioactive molecules used in tissue engineering vascularization and mentioned in this review. Lee et al, 2001;Gerhardt et al, 2003;Chiu and Radisic, 2010;Chow et al, 2010;Yuen et al, 2010;Shah et al, 2011;Zheng et al, 2012;Brudno et al, 2013;Nguyen et al, 2013;Alsop et al, 2014;Lai et al, 2014;Rich et al, 2014;Stamati et al, 2014;Wu et al, 2016;LaValley et al, 2017;Turner et al, 2017;Kuttappan et al, 2018;Stejskalová et al, 2019;Wang et al, 2019FGF Chow et al, 2010Tengood et al, 2011;Lai et al, 2014;Stamati et al, 2014;Kuttappan et al, 2018;Dong et al, 2019IGF Holland et al, 2005EGF Lai et al, 2014PDGF Tengood et al, 2011Brudno et al, 2013;Lai et al, 2014;Stejskalová et al, 2019;Wang et al, 2019Glycosaminoglycans Chow et al, 2010Chow et al, 2014;Wu et al, 2016 Frontiers in Bioengineering and Biotechnology | www.frontiersin.org as well as changing the method of retaining the drug (King and Krebsbach, 2012). Boontheekul et a...…”
Section: Degradation Dependent Releasementioning
confidence: 99%
“…For instance, increasing the cross-linking density of gelatin can improve molecule retention and limit its diffusion (Iwanaga et al, 2003;Patel et al, 2008). Turner et al (2017) crosslinked gelatin microspheres to drive a more regulated release of VEGF or BMP2, dependent on the progressive proteolytic degradation of the scaffold. The non-specific degradation of the scaffold only partially controls the delivery time of GF, making it necessary to develop more advanced systems, which will be discussed later.…”
Section: Degradation Dependent Releasementioning
confidence: 99%
“…Biomolecular species such as enzymes or metabolites also arbitrate the response of hydrogels. Turner et al (2017) [ 40 ] synthesized gelatin hydrogel microparticles (GHMs) at physiological pHs by the crosslinking reaction occurred via electrostatic interaction between anionic gelatin molecules and cationic vascular endothelial growth factors (VEGFs) or cationic bone morphogenetic protein 2 (BMP2) using genipin crosslinkers. The degradation of GHMs was derived by chromatographically purified collagenase (CLSPA collagenase), and the degradation behavior controlled the release behavior of VEGFs and BMP2s, which induce the expression of cells playing an essential role in osteoblast.…”
Section: Development Of Injectable Hydrogelsmentioning
confidence: 99%
“…Since then, a variety of studies of injectable hydrogels to be used in tissue engineering have been actively conducted for producing better repair effect. As like the studies on the injectable hydrogels for drug delivery, recently, multi-functional and hybrid as well as stimuli-responsive injectable hydrogels, are developing for tissue repair and regeneration [ 35 , 40 , 41 , 58 ].…”
Section: Therapeutic Applications Of Injectable Hydrogelsmentioning
confidence: 99%